Human Resource Planning in Nepalese Business Enterprises - Chaurasiya, Manoj Kumar (Academic Voices: A Multidisciplinary Journal, 2014)
Human resource planning is a process of determining organization’s future human resource requirements and course of action needed to satisfy those needs to achieve organizational objectives. It also ensure and determines that it has right number and right kinds of people at right places, at right time performing work in the organization effectively and efficiently for which they are most economical and useful . It tries to keep balance between organizations human resource supplied with required stable and capable people when they are demanded. This article deals with the concept, objectives, relevance of human resource planning. More ever it also identifies benefit to be taken by the use of human resource planning and highlights the human resource planning practices in Nepalese business enterprises. Academic Voices, Vol. 3, No. 1, 2013, Pages 24-27 DOI: http://dx.doi.org/10.3126/av.v3i1.9986